Porównanie do donatystów w nowożytnych polemikach wyznaniowych - Adamiak, Stanisław (Warszawskie Studia Teologiczne, 2017)
The paper shows how different polemists used the analogy with the fourth century Donatist schism to label their opponents in the Reformation controversies. The accusation of Donatism was raised not only by the Catholics against the Protestants in general, as opposing the authority of Rome, but also both by the Catholics and magisterial Reformers against the radical Reformers, who rejected any connection between the Church and the state, and demanded of their converts to be baptised again. The analogy was also used in the polemics between more and less radical branches of the English Reformation. It was also employed in a very efficient way by Cardinal Wiseman in 1839 against the Anglicans, and was one of the main impulses for the conversion of John Henry Newman to Roman Catholicism.